2012
DOI: 10.1115/1.4006535
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Radially Distorted Incident Flow on Performance of Axial-Flow Fans With Forward-Skewed Blades

Abstract: In this study, experiments and numerical simulations were carried out to evaluate the effects of radially distorted incident flow on the performance of axial-flow fans, which were equipped with three kinds of forward-skewed blades. Loss coefficient and velocity components at exit section as well as overall performance are discussed, both at the design point and the lower mass flow rate point. Furthermore, rotating stall was also observed by use of three dynamic pressure sensors. All results reveal that there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In this study, a commercial software CFX-Solver was used to solve the unsteady Reynolds-averaged Navier-Stokes equations with the help of SST k-ω turbulence model [19,20]. The second-order backward Euler scheme and the high-resolution scheme were adopted to discretize the temporal term and the convection terms, respectively.…”
Section: Computational Schemementioning
confidence: 99%
“…In this study, a commercial software CFX-Solver was used to solve the unsteady Reynolds-averaged Navier-Stokes equations with the help of SST k-ω turbulence model [19,20]. The second-order backward Euler scheme and the high-resolution scheme were adopted to discretize the temporal term and the convection terms, respectively.…”
Section: Computational Schemementioning
confidence: 99%
“…Gunn et al [28] investigated the effect of circumferential distortion on a fan stage operating at low speeds, reporting significant efficiency losses as a result of the large incidences on the blades along the entire annulus. A study on an axial fan with radial distortion blades identified that the modal waves leading to stall had a significant effect due to the flow near the hub region [29] . A few recent works have analyzed the characteristics of a high-aspect-ratio CRAF under radial and circumferential distortions [30,31] .…”
Section: Introductionmentioning
confidence: 99%
“…Chima [8] has computationally studied the performance of NASA stage 35 using a 3D unsteady code and found that the performance agreed well with the experimental results with radial distortion and shows reduction in the stable flow range of the compressor. Yang and Gu [9] have conducted experimental and computational investigations to evaluate the effects of radially distorted incident flow on the performance of an axial flow fan with three kinds of forwarded-skewed blades. The results reveal the beneficial effect of forward-skewed blade on the performance.…”
Section: Introductionmentioning
confidence: 99%